Crystalline phase control of BiVO4 thin films using RF sputtering. (10th March 2023) - Uezono, Namiki; Liu, Jiaqi; Pawar, Sachin A.; Islam, Muhammad Monirul; Ikeda, Shigeru; Sakurai, Takeaki
Abstract: A selective fabrication method for monoclinic-scheelite (m-s) BiVO4 and tetragonal-zircon (t-z) BiVO4 thin films using radio fRequency (RF) sputtering from a single target was developed. The kinetic energy of the sputtered atoms was controlled by varying the sputtering power to obtain BiVO4 films with m-s and t-z crystalline phases. Although the band gap of the t-z BiVO4 phase (3.0 eV) was larger than that of m-s BiVO4 (2.5 eV), the deposited t-z BiVO4 films showed a comparable photocurrent density (1.5 mA cm −2 ) at 1.23 V versus the reversible hydrogen electrode (400 W Xe lamp). This was mainly because of the reduced sputtering damage in the t-z BiVO4 crystal, which originated from the low sputtering power as well as the deep valence-band position in t-z BiVO4 that enabled the efficient utilization of the photocarriers. This work provides insights into crystalline phase control using the particle kinetic energy in sputtering.